The effects of a protein deficient diet on the mutagenicity and clastogenicity ofdumethynitrosamine and benzo(a) pyrene - Omwega, Abiud M.
Changes in the genetic materials (DNA) can occur either spontaneously or be induced by a physical, biological and chemical agent. The chemical compounds with mutagenic effects include those that require metabolic activation. Studies have shown that this activation can be affected by several factors such as chemical structure of the compound, route of administration, duration of treatment, distribution, environmental factors and nutrition. In this study, the effects of a protein deficient diet, fed ad libitum, on the mutagenic and cytogenic effect of dimethylnitrosamine (DMNA) and benzo(a) pryrene 9B(a)P) were examined. In vitro studies were done using the NAMRU strain of mice by the host-mediated assay (HNA) and the micronucleus test. In the HMA, DMNA and B(a)P were both shown to be mutagenic to the Salmonella G-46 after being metabolized by mice fed on the normal protein diet and also by those fed on the protein deficient diet. However, their mutagenicity was decreased by about 65% in the animals fed with the deficient diet. On the other hand, the ability of these mutacarcinogens to induce chromosomal aberrations was decreased by about 60% to levels equal to those expected to occur in spontaneous mutation, in the mice fed with the deficient diet. On examining the effects of the protein deficient diet on liver weight and liver microsomal constituents, it was found that liver weights are decreased by about 24% while microsomal protein and cytochrome P-450 contents are decreased by as much as 60%. In this way, a protein deficient diet is shown to reduce the mutagenic and cytogenic effects of both DMNA and B(a)P and the reductions parallel those of the cytochrome P-450 content in the liver microsomes.